2019
DOI: 10.1177/1533317519867824
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Pilot Study of Global Postural Reeducation Concerning the Cognitive Approach of Patients With Alzheimer’s Disease

Abstract: Background: Several recent studies have examined the positive effects of physical exercise and equilibrium on individuals with neurodegenerative diseases. Objectives: In this sense, this study based on an experimental design, tested whether global postural reeducation (GPR) can affect equilibrium and cognition, life quality, and psychological symptoms of patients with Alzheimer’s disease (AD). Methods: One hundred thirty-five participants with mild and moderate AD diagnosis were assigned to 2 groups: experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…These results agree with previous studies, which have shown the effectiveness of GPR treatment [11]. In other pathologies, GPR acts on muscle flexibility [9,[12][13][14][15][16]28,29], postural organization [3,29,30], functionality [6,20,23], quality of life [6,15,21,30,31], reducing pain [3,15,16,19], fatigue [23] and others [20,22,[32][33][34].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results agree with previous studies, which have shown the effectiveness of GPR treatment [11]. In other pathologies, GPR acts on muscle flexibility [9,[12][13][14][15][16]28,29], postural organization [3,29,30], functionality [6,20,23], quality of life [6,15,21,30,31], reducing pain [3,15,16,19], fatigue [23] and others [20,22,[32][33][34].…”
Section: Discussionsupporting
confidence: 91%
“…The LBP therapeutic approach for physical therapists should be a priority, since, according to the World Health Organization [10], it is not only a musculoskeletal health problem, but also involves other dimensions of the individual. In addition, is one of the most common health problems worldwide [3,4]. As described by Popescu and Lee [11], its prevalence is very high, reaching 84% in adults.…”
Section: Of 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Por este tipo de aspectos motores, el control de los mismos se vuelve aún más complejo, como se evidencia en usuarios con demencia, como en el estudio de Toots et al (2016): el 83 % de su población objeto fueron personas con enfermedad de Alzheimer, con dificultad concomitante en la transferencia de habilidades motoras por su alteración cognitiva. Se ha reportado también que, estas alteraciones generan más pérdida de la especificidad de la tarea y la funcionalidad, debido a la pobre capacidad para utilizar las habilidades adquiridas, en contextos nuevos (Todri et al, 2020), corroborando así la interacción balanceada que debe existir de estos procesos, para la consecución de un control postural óptimo y un movimiento que sea posible transferir a las situaciones cotidianas y las AVD.…”
Section: Movimiento Corporal Y Salud Mentalunclassified
“…Previous studies have shown the effectiveness of GPR treatment to be superior to physical therapy [12], and, according to the literature, the effects of GPR are quite broad in other pathologies, acting on muscle flexibility [9,[13][14][15][16][17][18][19], postural organisation [19][20][21][22], functionality [6,23,24], cognition, quality of life [6,16,21,25] and reducing pain [16][17][18]26], fatigue [24], and others [21,[27][28][29]. The benefits of GPR in AS, however, have been analysed either in conjunction with other types of treatment or were not studied in depth [4,30,31].…”
Section: Introductionmentioning
confidence: 99%